Diseño de un sistema semiautomático para el proceso de fabricación de vidrio templado en la Empresa Templus S.A.S. (2022)
In this research project, the glass tempering process was analyzed for a manufacturer of tempered safety glass, where initially the current state of the company and process, the production times (manufacturing and installation) and, in turn, the parameters and elements that could be key to the design of a semi-automatic system, with the aim of reducing production times by 20% (approximately 12 minutes) and thus human intervention in the glass tempering process. After that, the conceptual design of the semi-automatic system was developed, taking into account all the parameters analyzed, making a time study before and after the design, and verifying the approximate times that the semi-automatic system would execute for production. Finally, a maintenance manual for the designed semi-automatic system was made, where each of the elements is described with their respective preventive and corrective maintenance.